2021
DOI: 10.1038/s41598-021-85707-3
|View full text |Cite
|
Sign up to set email alerts
|

A postbiotic from Aspergillus oryzae attenuates the impact of heat stress in ectothermic and endothermic organisms

Abstract: Heat stress is detrimental to food-producing animals and animal productivity remains suboptimal despite the use of heat abatement strategies during summer. Global warming and the increase of frequency and intensity of heatwaves are likely to continue and, thus, exacerbate the problem of heat stress. Heat stress leads to the impairment of physiological and cellular functions of ectothermic and endothermic animals. Therefore, it is critical to conceive ways of protecting animals against the pathological effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
5
11
0
Order By: Relevance
“…Despite the lack of reduction of inflammatory markers, animal productivity improved in calves receiving the postbiotic. The latter agrees with beneficial effects of supplementing 3 and 6 g/d of AO postbiotic on productivity observed in previous work in heat-stressed lactating cows [11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite the lack of reduction of inflammatory markers, animal productivity improved in calves receiving the postbiotic. The latter agrees with beneficial effects of supplementing 3 and 6 g/d of AO postbiotic on productivity observed in previous work in heat-stressed lactating cows [11].…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with previous studies in ruminant and nonruminant animals for which heat stress increased markers of systemic inflammation [18,19,20]. However, our previous study in heat-stressed cows consuming AO postbiotic showed a quadratic reduction of serum amyloid A and lipopolysaccharides binding protein highlighting the effectiveness of 3 but not 6 g/d of postbiotic supplementation on markers of systemic inflammation [11]. Despite the lack of reduction of inflammatory markers, animal productivity improved in calves receiving the postbiotic.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several reports have shown an increase in the acute-phase protein haptoglobin, serum albumin A, and serum endotoxins in pigs exposed to heat stress for several hours or days [ 56 , 57 , 58 ]. In agreement with data from pigs, cattle exposed to elevated ambient temperature show greater plasma concentrations of acute-phase proteins (~34 °C 8 h/day for 7 to 21 days) [ 59 , 60 ]. Collectively, these results reveal activation of systemic inflammation during heat stress.…”
Section: What Components Of the Immune System Are Activated During Heat Stress?supporting
confidence: 86%
“…In recent years, probiotics and prebiotics such as yeast extracts or galacto-oligosaccharides (GOSs) have been promoted as feed additives to enhance immunity and GIT health [ 111 ] in heat-stressed cows [ 60 , 112 , 113 ], birds [ 49 ], and rats [ 108 ]. In most of these studies, the benefits in productive parameters, health, and welfare of the animals as a result of supplementation with pro- and prebiotics were examined.…”
Section: Nutritional Interventions To Avoid or Lessen The Effects Of Heat Stressmentioning
confidence: 99%